2015
DOI: 10.3390/md13116759
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antiviral Agents Targeting Hepatitis B Virus Promoter from Extracts of Indonesian Marine Organisms by a Novel Cell-Based Screening Assay

Abstract: The current treatments of chronic hepatitis B (CHB) face a limited choice of vaccine, antibody and antiviral agents. The development of additional antiviral agents is still needed for improvement of CHB therapy. In this study, we established a screening system in order to identify compounds inhibiting the core promoter activity of hepatitis B virus (HBV). We prepared 80 extracts of marine organisms from the coral reefs of Indonesia and screened them by using this system. Eventually, two extracts showed high in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The HBV inoculum used in this experiment was genotype D, and was derived from the culture supernatant of HepG2.2.15.7 cells30, which are a HepG2.2.15 subclone producing a high titer of HBV. HBV pregenome (pg) RNA and total HBV RNAs were detected in iPS-HLCs following inoculation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBV inoculum used in this experiment was genotype D, and was derived from the culture supernatant of HepG2.2.15.7 cells30, which are a HepG2.2.15 subclone producing a high titer of HBV. HBV pregenome (pg) RNA and total HBV RNAs were detected in iPS-HLCs following inoculation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HepG2.2.15.7 cells30, which are a HepG2.2.15 clone producing a higher level of HBV, were also cultured in DMEM/F-12-Glutamax (Invitrogen, Carlsbad, CA) supplemented with 10% FBS, 100 U/ml penicillin, 100 μg/ml streptomycin, 5 μg/ml insulin, and 10 mM HEPES. All cultures were maintained at 37 °C in a humidified atmosphere containing 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…Two sponge-derived polybrominated biphenyls 689,690 isolated from Indonesian Dysidea species were found to possess hepatitis antiviral activity with selectivity indices of 12.8-18.2. 691 Transcriptomic analysis of HepG2 hepatocarcinoma cells treated with both Crambe crambe metabolites crambescin C1 (ref. 692) and A1 (ref.…”
Section: Spongesmentioning
confidence: 99%
“…Examples include dysidaminones, which show nuclear factorkappa B (NF-κB) inhibitory activity 3) ; dysifragilones, which are nitric oxide (NO) inhibitors 4) ; dysidinoids, which possess anti-Methicillin-resistant Staphylococcus aureus (MRSA) activity 5) ; polybrominated diphenyl ethers (PBDEs), which have antiviral activity against hepatitis B virus 6) ; etc. 2,[7][8][9][10][11][12] In the course of our studies of novel bioactive molecules from coral reef organisms, 13) we have reported a series of cytotoxic spongian diterpenes from the soft white encrusting sponge D. cf.…”
mentioning
confidence: 99%